IL-6 and CRP response to maximal exercise intervention - Cipryan, L.; Svagera, Z.; Vala, R. (The Journal of Sports Medicine and Physical Fitness, 2015)
AIM: The purpose of this study was to investigate the recovery pattern of the plasma inflammatory markers interleukin-6 (IL-6) and C-reactive protein (CRP) after the single-bout maximal exercise. The exercise of different type (continuous vs. intermittent) was performed and also compared in this study.